GENDER DİFFERENCES İN EMOTİONAL İNTELLİGENCE: PROBLEMS AND ANALYSES - Babayeva, Firangiz (Revista Gênero e Interdisciplinaridade, 2025)
The article analyzes gender differences in emotional intelligence. The article shows that emotional intelligence is a fundamental element of human behavior and manifests itself in various forms. Studies show that the level of emotional intelligence differs in boys and girls. In addition, it was found that those with higher emotional intelligence are more resilient, which allows them to better adapt to changes in stressful situations. The conducted study showed that gender differences in the emotional intelligence of an individual in students have been empirically determined. It has been proven that during the student period, the indicators of emotional intelligence in groups of boys and girls differ significantly. Boys understand and manage their emotions better, and have a higher level of self-control. Girls demonstrate the ability to understand and manage the emotions of people around them. The results obtained can be used to understand the main aspects of psychological support for students who experience certain difficulties in choosing behavioral patterns. In conclusion, the author concludes that the level of emotional intelligence is higher in girls than in boys.